2021
DOI: 10.3390/app11178089
|View full text |Cite
|
Sign up to set email alerts
|

Vibrations of Misaligned Rotor System with Hysteretic Friction Arising from Driveshaft–Stator Contact under Dispersed Viscous Fluid Influences

Abstract: Dynamic analysis of a combination of misaligned rotors, the disturbance of the Cardan joint and the rotor–stator rubbing within a restricted clearance space in a viscous fluid is complex and can result in persistent vibration anomalies that are often misunderstood. It becomes increasingly important to gain some insights into how the transmission of coupled motion responds dynamically under a variety of conditions. This paper introduces an efficient simulation of the misaligned multi-degree-of-freedom rotor’s m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Transmission shafts are a common component of both vehicles and locomotives. If it can be done without increasing costs or sacrificing quality and dependability, reducing the weight of the Cardan (drive) shaft can play a part in the overall weight reduction of the vehicle [23]. Using different stacking sequences, it is feasible to create a modified Cardan shaft with reduced weight, increase the shaft's natural frequency, and reduce bending stresses.…”
Section: IImentioning
confidence: 99%
“…Transmission shafts are a common component of both vehicles and locomotives. If it can be done without increasing costs or sacrificing quality and dependability, reducing the weight of the Cardan (drive) shaft can play a part in the overall weight reduction of the vehicle [23]. Using different stacking sequences, it is feasible to create a modified Cardan shaft with reduced weight, increase the shaft's natural frequency, and reduce bending stresses.…”
Section: IImentioning
confidence: 99%
“…where μ that depends on θ 1 and ψ 1 is a small perturbation parameter modelled on the basis of Hooke's joint kinematics and expressed in detail in [23] and…”
Section: Expression Of the Governing Equations Of The Crackedmentioning
confidence: 99%
“…In the current work, a model for analyzing the high vibrations of a Cardan shaft focusing on coupling malfunctions and extracting the features of a cracked driveshaft system coupled to a single Hooke's joint in a viscous fluid is developed. Earlier works [16,[20][21][22][23] have shown that resistance fluid has a significant impact on rotor system behaviour, and the wavelet technique is an effective signal processing tool for crack detection, which will be used here for crack feature extraction in a fluid medium. e use of the rotating reference frame will assist in a better understanding of the nature of the shaft whirl and facilitate the shaft modelling and the fluid-driveshaft coupling.…”
Section: Introductionmentioning
confidence: 99%
“…Many valuable studies [6][7][8] have been conducted on the application of eccentric shafts in existing literature, but this does not mean that the eccentric shaft is perfect. Actually, in its practical applications, the mechanical failure [9][10][11] has widely found that the actual speed of a desktop shaker intermittently exceeds the set speed after prolonged use, which corresponds to busting oscillations [12][13][14] in the rotor-oscillator system and can be named overspeed oscillation. Diferent from other current research work focusing on the application of eccentric shaft technology, the main task of this paper is to study defects, causes, and solutions of it.…”
Section: Introductionmentioning
confidence: 99%